(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In machine age, people were ancillary and things werecentral but in information age, things are ancillary and knowledge is central.A company’s value derives not from things but from knowledge, know-how,intellectual assets, and competencies – all embedded in people. Change,complexity and competition are buzzwords in today’s business environment. Aturbulent business environment, highly demanding customers, formidablecompetitors, technological innovations, shortening product life cycles and lowbarriers to entry, have forced organizations to put a higher emphasis onlearning. Organizations are becoming more fluid, facilitating networks ofcustomers, suppliers and business partners. Boundaries of organizations arebecoming blurred and departmental barriers are fading. Corporations arebecoming flatter and leaner. Empowerment is replacing power and revolutionarychange is swapping with incremental change. The companies now have to find andretain their positions not only in local or national market but also have toexplore markets worldwide. To survive, prosper and succeed in current businessenvironment, the organizations have to be proactive instead of being reactive.The need of the hour is to think the unthinkable, try what seems to beimpossible, put your best to bring forth novel ideas and then implement them torevolutionize the world.